When solving system equations, we can use substitution method or elimination. Today I'm using substitution method.
First name the 2 equations.
3x + y = 3 (1)
x + y = 2 (2)
Now pick one equation and express one algebra in forms of the other.
From (2),
x = 2 - y (3)
Now substitute (3) into (1),
3(2-y) + y = 3
6 - 3y + y = 3
6 - 2y = 3
6 - 3 = 2y
y = 1.5
Now substitute y = 1.5 into (2)
x + 1. 5 = 2
x = 2 - 1.5
x = 0.5
Therefore the answer is x = 0.5 and y = 1.5
Answer:
0.4
Step-by-step explanation:
15 = 5p - 13
-13 = 5p -13
---------------- ( subtract 13 on both sides )
<u> 2 = 5p</u>
5 = 5p
---------------- ( divide 2 by 5 )
p = 0.4
( p equals 0.4 )
Answer:
The answer is 3.4
Step-by-step explanation:
5 or more, round up
4 or less, round down
rounding 6
round up
so...
3.4
(-2, -7) and (-4, -9)
Answer:
0.84 is the answers for the question
Step-by-step explanation:
please give me brainlest
Answer:
-1 1/3 hope this helps
Step-by-step explanation: